Pex4Fun: Cloud Computing in the CS Classroom - Tillmann, Nikolai; Halleux, Jonathan "Peli" de (The Voice of K-12 Computer Science Education and Its Educators, 2011)
CSTA is working on a new document that will update the comprehensive learning standards for K–12 computer science (CS) education.